(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Assess the analytical performance of several peripheral blood cell indices on the DxH 690T system using the Six Sigma method. Method: Cross-sectional descriptive study of White Blood Cell count (WBC), Red Blood Cell count (RBC), Hemoglobin (HGB), and Platelet count (PLT) indices from October 2024 to March 2025 at the Department of Laboratory Medicine of Vinmec Smart City International Hospital. Results: Based on Sigma values, the quality of the indices is classified as follows: 9 indices have excellent quality, accounting for 75%. There is 1 index with good quality, accounting for 8.3%, and 2 indices with acceptable quality, both accounting for 16.7%. Conclusion: The Six Sigma method is a valuable tool in laboratory quality management, enabling laboratories to assess analytical performance and improve testing quality.